THE IMPACT OF TEACHING METHODS AND LEARNING MOTIVATION ON DRIBBLING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Taufik Taufik; Amir Amir; Aschari Senjahari Rawe (International Journal of Teaching and Learning, 2025)
The aim of this research is to determine: (1) The dribbling learning outcomes of students taught using an inclusive teaching style and those taught using the practice method (2) The influence of the interaction between teaching style and learning motivation on the skills of dribbling learning outcomes. (3) differences in ball dribbling results for students taught using an inclusive teaching style and those taught using the practice method for new students in terms of low achievement motivation. (4) differences in ball dribbling results for students taught using an inclusive teaching style and those taught using the Barru method in terms of high achievement motivation. This type of research is true experimental with factorial design. This research used two classes, namely a class taught using an inclusive teaching style and a class taught using the practice method. Research result. (1) There are differences in the learning outcomes of dribbling for students taught using an inclusive teaching style and those taught using the practice method for students at SMP Negeri 2 Barru.  (2) There is an interaction effect between teaching style and learning motivation on the ball dribbling learning outcomes of students at SMP Negeri 2 Barru. (3) There are differences in the dribbling results of students who are taught using an inclusive teaching style and those who are taught using the practice method for students in terms of low achievement motivation. (4) There is a difference in the dribbling results of students who are taught using an inclusive teaching style and those who are taught using the practice method for students in terms of high learning motivation.